(untitled) (Anclajes, 2025)
Studies on the plebeian, the popular and the drifts of the significant “people” have had a sustained flow in recent years. For this inflection is proposed the name “popular turn”, which is linked to previous appearances of these problems, but as a form of realization whose main feature implies a further politicization. It is presented a series of works linked to this area of ​​studies that, from academic writing and research, a way of intervention and reflection that is thought in the present time, based on the current situation which the humanities meet. To this end, the articles included work on dissimilar literary objects from diverse periods with the conviction that a study such as the one undertaken can only be successful under multiple and plural perspectives and temporalities.